Selected Decisions and Selected Documents of the International Monetary Fund, 40th Issue Supplement. (Selected Decisions; Issue, Year, 2020)
The Fund's Legal Department has produced this Supplement to Selected Decisions and Selected Documents of the IMF, 40th Issue, with the aim of making available in convenient form selected policy decisions and documents issued after the publication of the 40th Issue but before the issuance of the forthcoming 40th Issue.